Market participants or the random walk: Who forecasts better? Evidence from micro-level survey data - Tamás Kiss; Kamil Kladivko; Oliwer Silfverberg; Pär Österholm (Örebro University School of Business, 2023)
We analyse micro-level data concerning four financial variables in Sveriges Riksbank's Prospera Survey to evaluate the accuracy of forecasts provided by professionals active in the Swedish fixed-income market. Our results indicate that for the SEK/EUR and SEK/USD exchange rates, and the five-year government bond yield, none of the market participants that frequently participate in the survey manage to significantly outperform the random-walk forecast. For the central bank's policy rate, the market participants typically have a statistically significant higher forecast accuracy than the random-walk forecast at the three-month horizon; however, at the two- and five-year horizons, the random-walk forecast typically outperform the market participants.
Keywords: E47; G17; 330; Out-of-sample forecasts; Exchange rates; Interest rates